2009
DOI: 10.1136/ard.2008.099655
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the GDF5 region is associated with osteoarthritis, height, hip axis length and fracture risk: the Rotterdam study

Abstract: This population-based study shows that GDF5 gene variants are associated with hand OA, knee OA and fracture risk in elderly women. It also replicates previous association between GDF5 variation and height. Furthermore, our findings for HAL suggest that GDF5 action is primarily directed to the long bones, rather than the axial skeleton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…The reduced activity of GDF5 may inhibit the process of early cartilage differentiation (Hatakeyama et al, 2004). Genetic variations in the GDF5 locus have been reported to be involved in the pathogenesis of rheumatoid arthritis and to influence human height, hip axis length and fracture risk in the elderly (Rouault et al, 2010;Vaes et al, 2009). Furthermore, association of variant T allele with other musculoskeletal phenotypes, including variation in Achilles tendon pathology, fracture risk and congenital dysplasia of the hip, has also been reported (Posthumus et al, 2010;Sanna et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The reduced activity of GDF5 may inhibit the process of early cartilage differentiation (Hatakeyama et al, 2004). Genetic variations in the GDF5 locus have been reported to be involved in the pathogenesis of rheumatoid arthritis and to influence human height, hip axis length and fracture risk in the elderly (Rouault et al, 2010;Vaes et al, 2009). Furthermore, association of variant T allele with other musculoskeletal phenotypes, including variation in Achilles tendon pathology, fracture risk and congenital dysplasia of the hip, has also been reported (Posthumus et al, 2010;Sanna et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The same has been observed in the BMP-signaling pathway (another key developmental pathway). Mutations in the GDF5 gene result in severe chondrodysplasia and skeletal malformations (23), and a milder variant that influences GDF5 expression levels, results in a slightly elevated risk for knee OA later in life (2,24).…”
Section: Discussionmentioning
confidence: 99%
“…These findings represent the first highly significant evidence for an OA susceptibility gene that affects diverse ethnic groups. 33 Vaes et al 34 studied the association between rs143383 and radiographic OA in hands, knees and hips, together with height, bone size parameters and fracture risk, in a population-based cohort that consisted of a total of 6365 Caucasians. The authors found the association of GDF5 with knee OA, height, bone size and fracture risk in women; however, no associations with hip OA or BMD (Bone Mineral Density) were detected, and no associations were observed in men.…”
Section: Gdf5mentioning
confidence: 99%